International cargo insurance - Dunt, John (Lloyd's shipping law library, 2012)
Examines the law and practice of marine cargo insurance on a worldwide basis, and provides the busy practitioner information needed to quickly and accurately resolve cargo insurance coverage issues, wherever they may arise. This book focuses on the law in the United States and England